Smrti-sugandha - Desai, Ishwarlal Ichharam, 1903- (Kasturabā Sevāśrama, 1975)
Festschrift honoring Kalyāṇajī Viṭhṭhalabhāī Mahetā, 1890-1973, and Mīṭhubahena Pīṭīṭa, 1892-1973, Gandhian social and political activists of Gujarat.